Consumer Price Index Analysis as Teaching Material for Accounting Students - Jansaris Othniel Purba (Reflection: Education and Pedagogical Insights, 2023)
The Consumer Price Index (CPI) is a crucial economic indicator that measures changes in the average prices of a basket of goods and services purchased by households over time. This paper aims to highlight the significance of incorporating Consumer Price Index analysis into the curriculum of accounting students. This study uses descriptive analysis to explain conditions regarding inflation to students. The incorporation of Consumer Price Index (CPI) analysis as a teaching material for accounting students is of utmost importance. This economic indicator plays a vital role in measuring inflation rates and understanding the macroeconomic environment that businesses operate within. By familiarizing themselves with the CPI and its implications, accounting students can better comprehend the impact of inflation on financial reporting, budgeting, forecasting, and investment decision-making. By incorporating case studies and practical applications of CPI analysis, accounting students can gain hands-on experience and strengthen their analytical skills. This approach not only enriches their learning but also equips them with practical tools to navigate the complexities of the dynamic business world.